Experiment Result of High Frequency Switching SiC Mosfet Gate Driver - Kurniawan, Agta Wijaya; Firmansyah, Eka; Wijaya, F. Danang (2022)
DC-DC converter battery charger application commonly applied a high-frequency switching method. The high-frequency technique aims for a smaller size transformer size and weight. Overall, the chosen strategy leads to more economical end-product. The SiC-MOSFET becomes an additional solution to achieve high power and high frequency application applications. This paper focused on the design of the gate driver for SiC-MOSFET that can be applied in many applications including battery charger and inverter applications. The result showed that the gate driver designed had successfully switched SiC-MOSFET up to 35 kHz.